Cariotipos de los murciélagos vampiros (chiroptera: desmodinae) (1976)
Vampire bats are clearly members of the family Phyllostomatidae but their affinities within the family are less obvious. Investigations into the karyotypes of the three monotypic genera (Desmodus, Diaemus and Diphylla ) were made to determine if chromosomal data might reveal the phylogenetic affinities of the subfamily Desmodinae.  The karyotypes of two genera have been described. In this paper we describe the karyotype of Diphylla, discuss the intrasubfamiIial variation and compare the karyotypic data of the Desmodinae to that of other subfamilies of the Phyllostomatidae.